Просторова організація та функціональне зонування засобів розміщення у планувальній структурі сучасного міста (на прикладі м. Чернівці) - Круль, Галина Ярославівна; Заячук, Оксана Григорівна; Смик, Оксана Степанівна (Економіка та суспільство, 2026)
This study examines the pressing issue of the spatial organization and functional zoning of accommodation facilities within the planning structure of a modern city, using Chernivtsi as a case study. The relevance of the study stems from the transformation of hotel real estate from a simple element of the service sector into an active factor that shapes the urban landscape and significantly influences the transportation infrastructure, architectural appearance, and functional balance of the urban environment. In the context of Chernivtsi’s dual status as a UNESCO World Heritage Site and a strategic transit hub near the border with the EU, the need to balance the preservation of historical heritage with the development of modern infrastructure becomes extremely important. The main objective of this study is to provide a scientific rationale for a hotel location model that ensures the effective operation of the hotel industry while preserving the authenticity of the historic urban fabric. The research methodology is based on a systematic approach that involves the use of cartographic analysis, field observations, and statistical monitoring of online booking systems (Booking.com and Hotels24.ua) to assess the current state of the market as of 2026. Comparative and functional-spatial analysis methods were applied to classify 42 hotels, 6 hostels, and over 50 apartment-style establishments into distinct territorial clusters. The study’s results identify four key zones of accommodation concentration: the historic center, residential areas, the peripheral (trans-commercial) zone, and suburban recreational centers. It has been established that, although the historic center remains the main hub for cultural and business tourism, it faces serious infrastructure constraints, such as a lack of parking spaces and limited accessibility for people with disabilities. In residential areas, hotels have become hubs of local infrastructure, while peripheral facilities have reoriented toward MICE tourism and logistics support. A significant shortage of budget hostels for young people in the city center has been identified as a key opportunity for growth. The practical value of this article lies in providing a foundation for strategic urban planning and the optimization of tourism infrastructure, as well as in offering specific recommendations for diversifying accommodation types and reducing the anthropogenic load on the city’s historic core.
Spatial organization and functional zoning of accommodation facilities in the planning structure of a modern city (case study of Chernivtsi)
Keywords: готельна інфраструктура; планувальна структура міста; функціональне зонування; просторова організація; засоби розміщення; Чернівці